2020
DOI: 10.1016/j.jtemb.2020.126452
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between soil arsenic concentration and mortality from alzheimer’s disease in mainland China

Abstract: Objectives: The current study was designed to investigate the relationship between the soil arsenic (As) concentration and the mortality from Alzheimer's disease (AD) in mainland China. Study design: Ecological study. Methods: Twenty-two provinces and 3 municipal districts in mainland China were included in this study. The As concentrations in soil in 1990 was obtained from the China State Environmental Protection Bureau; the data on annual mortality of AD from 1991 to 2000 were obtained from the National Deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In vivo studies showed that excessive exposure to As induced neuronal apoptosis, which interrupted the neurodevelopment and cognitive functions of rats [ 163 , 164 , 165 ]. Epidemiological studies in rural-dwelling adults and elders also show that As (3–15 µg/L) levels in water negatively correlated with the scores of cognitive performance and memory, indicating that As is a neurotoxic metalloid [ 166 ], which also acts as a risk factor for AD [ 33 , 167 , 168 , 169 ]. However, the mechanisms of As-induced neurotoxicity remain unclear.…”
Section: Molecular Mechanisms Of Metal-induced Mitochondrial Dysfunctionmentioning
confidence: 99%
“…In vivo studies showed that excessive exposure to As induced neuronal apoptosis, which interrupted the neurodevelopment and cognitive functions of rats [ 163 , 164 , 165 ]. Epidemiological studies in rural-dwelling adults and elders also show that As (3–15 µg/L) levels in water negatively correlated with the scores of cognitive performance and memory, indicating that As is a neurotoxic metalloid [ 166 ], which also acts as a risk factor for AD [ 33 , 167 , 168 , 169 ]. However, the mechanisms of As-induced neurotoxicity remain unclear.…”
Section: Molecular Mechanisms Of Metal-induced Mitochondrial Dysfunctionmentioning
confidence: 99%
“…However, the hypothesis and molecular mechanisms of arsenic-related pathology in Alzheimer are still unclear 5 . In an ecological study by Li et al 27 , the association between exposures to contaminated soil and the death rate due to Alzheimer was investigated, and the relative risk (RR) and Spearman's correlation coefficient were calculated using based on10-year Alzheimer's mortality data. Based on the results, in the areas where the average concentrations of arsenic were 9.05, 10.4, and 13.1 μg/L, relative risks were calculated and found to be 4.3 (CI 4.3–4.39), 6.1 (CI 6.04–6.17), and 9.1 (CI 9.03–9.2), respectively 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies that analyzed serum arsenic did not find an association with AD [ 44 , 45 ], while greater arsenic in nail and hair of AD patients was reported [ 46 ]. There is evidence that arsenic accumulates in the brains of rodents [ 47 , 48 ] and humans [ 49 , 50 ]. Exposure to arsenic causes brain damages such as neuronal necrosis and apoptosis [ 51 ], oxidative stress [ 52 ], Tau hyperphosphorylation [ 28 ], and transcriptional activation of Aβ precursor protein gene [ 53 ].…”
Section: Discussionmentioning
confidence: 99%